Stability and moduli spaces of syzygy bundles - Macias Marques, Pedro (2011)
It is a longstanding problem in Algebraic Geometry to determine whether a syzygy bundle on the projective space defined as the kernel of a general epimorphism given by homogeneous forms is (semi)stable. In this thesis, attention is restricted to the case of syzygy bundles associated to n generic forms of the same degree d.